2009
DOI: 10.1002/ceat.200800558
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Circulation Velocity in a Spouted Bed Apparatus with Draft Tube

Abstract: Measurements of spouting characteristics were carried out in an apparatus consisting of two conical sections connected to a cylindrical section. Inside the lower conical section a draft tube was fixed. Results of minimum circulation velocity were obtained for an apparatus equipped with a draft tube of different inside diameters and lengths for different kinds of particles as well as for different static bed heights. Experimental data have been further analyzed to develop new correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…In fact, the inlet diameter should be smaller than 20–30 times the average particle diameter in order to avoid a slugging regime and achieve spouting status. Draft tubes are used to achieve stability out of this range, but they change the hydrodynamics and solid circulation rate of spouted beds. The lower conical section of the contactor performs differently when the draft tube is used and depends largely on the bed geometry, draft tube diameter, length of the entrainment zone, and operating conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…In fact, the inlet diameter should be smaller than 20–30 times the average particle diameter in order to avoid a slugging regime and achieve spouting status. Draft tubes are used to achieve stability out of this range, but they change the hydrodynamics and solid circulation rate of spouted beds. The lower conical section of the contactor performs differently when the draft tube is used and depends largely on the bed geometry, draft tube diameter, length of the entrainment zone, and operating conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…It is well known that to properly predict the behavior of a system by the MLP network, a rather large amount of experimental data points is essential , . From previous works published in the literature, it can be concluded that the minimum spouting velocity in conical spouted beds equipped with a draft tube is affected by different parameters, such as the acceleration of gravity, the gas viscosity, the particle diameter, the bed cone angle, the gas inlet diameter, the static bed height, the draft tube diameter, the entrainment zone length, and the length of the tube , , . The mentioned geometric factors are illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Su et al [10] analyzed the effects of operating conditions and geometrical parameters on the flow behavior, and found that the minimum spout-fluidizing velocity increases with increasing the length of entrainment zone and the draft tube diameter, but it decreases with the increasing of fluidizing gas flow rate and static bed height. However, Kmiec et al [1] showed that the minimum circulation velocity is dependent on the static bed height and on the level of the upper edge of the draft tube based on their apparatus. Wang et al [11] on the other hand, studied the flow behavior of particles in a two-dimensional spouted bed with a draft tube using a continuous kinetic-friction stresses model.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, in many applications of fluidized beds, extract thermal energy is required, leading to demands of specified design of reactor [2]. Therefore, finding new reactor more energy-efficient is an important factor in the proper design of industrial fluidized beds [1][2][3]. Developed by School of Technology, Beijing Forestry University [4], the annular fluidized-bed reactor combines a cylinder furnace into a fluidized-bed, which is also encircled by a cylinder vessel, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation